One-step fabricated Fe3O4@C core–shell composites for dye removal: Kinetics, equilibrium and thermodynamics. (March 2015) - Qu, Lingling; Han, Tingting; Luo, Zhijun; Liu, Cancan; Mei, Yan; Zhu, Ting
Abstract: B-Fe3 O4 @C core–shell composites were synthesized via one-pot hydrothermal carbonization (HTC) process and used as an adsorbent for the removal of methylene blue (MB) from aqueous solution. By using sodium borate as the catalyst, the hydrothermal carbonization process of B-Fe3 O4 @C core–shell composites was optimized and a higher surface area was obtained. The adsorbent was characterized by XRD, Raman spectra, SEM, TEM and N2 adsorption/desorption isotherms. We studied the dye adsorption process at different conditions and analyzed the data by employing the Langmuir and Freundlich models, and the equilibrium data fitted well with both models. Kinetic analyses were conducted by using the Lagergren pseudo-first-order and pseudo-second-order model and the results showed that the adsorption process was more consistent with the pseudo-second-order kinetics. To better understand the dye adsorption process from the thermodynamics perspective, we also calculated Δ H ο, Δ S ο, Δ G ο and E a, the results suggesting that the MB adsorption process was physisorption endothermic process, and spontaneous at room temperature. The as-synthesized B-Fe3 O4 @C showing high magnetic sensitivity provides a facile and efficient way to recycle from aqueous solution. Highlights: Fe3 O4 @C was synthesized via one-pot hydrothermal carbonization (HTC) process. By using sodium borate as catalyst, the surface area of B-Fe3 O4 @C was increased. B-Fe3 O4 @C exhibits an enhanced adsorption capacity over Fe3 O4 @C.